DETEKSI DELESI GEN DAZ (Deleted in AZoospermia) PADA PRIA AZOOSPERMIA DENGAN METODE PCR (Polymerase Chain Reaction) - V.A. Ferandra; Sukarjati Sukarjati (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
At this time the case of azoospermia is quite common in infertile men. Azoospermia is a condition where the semen does not contain sperm. Many causes azoospermia, including the deletion of a gene at the locus that is located on the Y chromosome long arm (YQ) known as AZF gene (Azoospermia Factor). One of the genes in the AZF region are genes that AZFc DAZ (Deleted in Azoospermia). The purpose of this study was to detect the presence of the DAZ gene deletions in men with azoospermia cases using PCR (Polymerase Chain Reaction). The study design was descriptive. Venous blood samples with EDTA anticoagulant taken from 10 men azoospeermia then extracted to obtain DNA. DNA samples were then carried out PCR with primers DAZ. The PCR products were separated by electrophoresis in 2% agarose gel and visualized using UVtranslluminator. Of the 10 samples, four patients including DAZ gene deletion was detected experience while the other six do not experience DAZ gene deletions. It concluded that found their DAZ gene deletions in men with azoospermia using the PCR method